PARTIKEL PENEGAS NANKA DALAM BAHASA JEPANG - Elizabeth Ika Hesti Nindya (Diponegoro University, 2017)
This study examines the structure and significance of nanka toritatejoshi. The method used is literature study. Nanka is a toritatejoshi particle that is fully functional of the element attached to it and adds a sense of judgment to the element it attaches. The nanka toritatejoshi can increase the nouns, verbs, adjectives, pronouns persona, nominal phrases, and nominal clauses and add to the meanings of underestimation, impossibility, and condescending feelings.